ʺTeaching Ukrainian as a Foreign Language in Multinational and Mononational Student Groups of Engineering and Engineering-Pedagogical Specialities: Priority Methods and Specific Featuresʺ. - Rotova, N. (Problems of Engineer-Pedagogical Education, 2024)
The article reveals the peculiarities of teaching Ukrainian as a foreign language in mono-ethnic and multinational groups. The nature, methods and techniques of organising work in such groups differ considerably. There are several reasons for these differences, and knowledge and understanding of them will help the teacher to organise his or her work competently and effectively. Students who are part of homogeneous national groups are initially determined to create an atmosphere of mutual assistance and friendly support for their compatriots in the classroom ˗ direct participants in the learning process. Foreign students, united on the basis of territorial, cultural, religious, and everyday commonalities, usually have a strong desire to maintain an open, conflict-free communication situation in the classroom. A complicating factor in mastering the Ukrainian language in groups with a single nationality is the lack of need to use Ukrainian outside of class and to express their own real needs. Speaking about multinational study groups, it should be noted that they increase students' motivation to speak Ukrainian not only in class but also outside of class (provided there is no intermediary language), and this is an undoubted advantage of joint learning by representatives of different countries and cultures. A teacher working in an international group needs to take into account the national characteristics of students, which should be manifested in the selection of educational material, the choice of the optimal way of presenting it and the effective way of working on complex phenomena of Ukrainian grammar, as well as in anticipating typical mistakes and difficulties that each student may encounter. It is necessary to closely monitor the psychological situation in the classroom, to prevent the emergence of hostile attitudes towards each other among students belonging to different national and cultural communities, to prevent in every possible way the manifestation of a sense of superiority of one nation over another, because possible interpersonal conflicts on national and religious grounds at the very beginning of training can significantly reduce the pace of learning the material and further negatively affect the level of students' learning.